Cutting-edge development in dendritic polymeric materials for biomedical and energy applications - Thalji, Mohammad R.; Ibrahim, Amal Amin; Ali, Gomaa A. M. (Elsevier Ltd., 2021)
Dendritic polymers (dendrimers and hyperbranched polymers) are becoming increasingly popular due to their vast range of uses. Due to their distinctive and novel qualities, they have demonstrated a strong interest. Since its discovery, dendritic polymers have become a potential material for many research applications, ranging from biomedical and tissue engineering to catalytic and energy applications. Since then, dendritic polymers' unique features have become a promising platform for a variety of uses. Dendritic polymers have made great progress in overcoming basic and technological problems related to their biomedical and energy applications. This review summarizes the strategies of synthesizing dendrimers and hyperbranched polymers. Further, the review highlights the applications of dendrimers and hyperbranched polymers in many study fields such as drug delivery, gene delivery, tissue engineering, catalysis, and energy storage. This review concludes with future avenues to be explored for the applications of dendritic polymers.